Analisis Kapasitas Drainase Perumahanan Pesona Citra Cemerlang 2 Kota Tarakan Menggunakan EPA SWMM 5.1 - Rahmat Faizal (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Borneo Tarakan, 2021)
SWMM is a rain-runoff simulation model that is used to simulate the quantity and quality of runoff from urban areas. Based on the evaluation using SWMM software at Pesona Citra Cemerlang 2 Housing, it was found that the drainage system in the long sections JU29-O5, JU4-O8, and JU5-O8 could not accommodate rainwater runoff. This is influenced by the dimensions of the drainage channel which cannot accommodate the existing water runoff and thick sediment deposits that cover the drainage channel so that the capacity is reduced, consequently if it rains it will cause puddles of water at several points in Tarakan City. So to overcome the puddle, it is necessary to change the dimensions of the channel and routinely dredge the sediment deposits that cover the drainage channel